1980
DOI: 10.1111/j.1570-7458.1980.tb02942.x
|View full text |Cite
|
Sign up to set email alerts
|

THE “BIOTYPES” OF THE RICE BROWN PLANTHOPPER, NILAPARVATA LUGENS

Abstract: From previous studies, the biological nature of the so‐called biotypes of N. lugens is obscure. Experiments on biotypes 1, 2 and 3 from the Philippines demonstrated that they lacked significant breeding barriers. Inbred biotype cultures showed considerable variation and overlap between each other in virulence. A field population from the Philippines was similarly variable and included individuals which could be attributed to different biotypes. It is concluded that the use of the term biotype in this species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 8 publications
5
60
0
2
Order By: Relevance
“…BPH1 is the first identified BPH resistance gene, and the resistance was broken down by the BPH biotype 2. Then, BPH2 was identified to resist BPH biotype 2, but the resistance was overcome by BPH biotypes 3 later (10,11). In this study, we showed that BPH1/9-7 and -9 are alternative allelotypes in this locus that confer resistance to BPH biotypes 1, 2, and 3.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…BPH1 is the first identified BPH resistance gene, and the resistance was broken down by the BPH biotype 2. Then, BPH2 was identified to resist BPH biotype 2, but the resistance was overcome by BPH biotypes 3 later (10,11). In this study, we showed that BPH1/9-7 and -9 are alternative allelotypes in this locus that confer resistance to BPH biotypes 1, 2, and 3.…”
Section: Discussionmentioning
confidence: 68%
“…In 1981, another BPH population (biotype 3) capable of overcoming resistance of BPH2 was detected. It is now known that wide variation in virulence occurs in BPH populations (10,11).…”
mentioning
confidence: 99%
“…In fact, the principal defence mechanism of resistance genes is to cause direct or indirect inhibition of feeding behaviour although inhibition of feeding behaviour has multiple effects on BPH, including lower survival, prolonged nymphal periods, lower weight and reduced oviposition [8,23,41,42]. Even if a simple genetic mechanism mediated by a major virulence gene controls the qualitative difference in BPH responses between 'biotypes', this genetic parsimony might have been masked in wild BPH populations by high levels of genetic diversity and/or heterogeneity [7,22,23,43].…”
Section: Discussionmentioning
confidence: 99%
“…The longer lasting resistance of these genes reflects variation in the adaption ability of BPH populations to resistance genes. Therefore, the breeding and deployment of new resistant rice varieties should be considered in the context of genetic and physiological mechanisms of BPH adaptation to rice resistance [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…The great majority are moderately resistant and a few highly antibiotic. There are no confirmed reports of insect resistance 'breakdown' given the emergence of new sogata biotypes, in contrast to the appearance of successive biotypes of the brown planthopper Nilaparvata lugens [66] in tropical Asia, presumably caused by the release of monogenic, highly antibiotic resistance.…”
Section: Genetic Resistancementioning
confidence: 98%